OHSAS 18001 Step by Step : a Practical Guide - Sadiq, Naeem (IT Governance Publishing, 2012)
"In this easy-to-understand and timely pocket guide, Naeem Sadiq, examines the practical and managerial issues an organisation faces as it gears up to meet OHSAS 18001 standards of occupational health and safety"--EBL